A cross-sectional study of knowledge about secondhand smoke-attributed diseases, awareness, and applicability of the smoking control law in a southern province of Thailand - Chutarat Sathirapanya; Napakkawat Buathong; Polathep Vichitkunakorn; Phoomjai Sornsenee; Vasin Pipattanachat; Pornchai Sathirapanya (Tobacco Induced Diseases, 2025)
Introduction Secondhand smoke (SHS) exposure is a significant cause of illness. This study aimed to explore the awareness of SHS-attributed illnesses and the legal control of the Tobacco Product Control (TPC) Act 2017 among the local people living in Meung district, a municipality of Songkhla Province, Thailand.